Visible amplitude: Towards quantifying prominence in sign language. (November 2019) - Tkachman, Oksana; Hall, Kathleen Currie; Fuhrman, Robert; Aonuki, Yurika
Highlights: To-date, there is no easily obtainable, objective measure to quantify sign language prominence. Visible amplitude quantifies movement contained on a frame-by-frame basis in a video. Visible amplitude can be used as a measure of sign language prominence. Certain sublexical characteristics of the sign contribute significantly to visible amplitude. Long-standing claims about signs' distribution can be tested using this measure. We also propose possible future applications of this measure. Abstract: While there has been some prior work on what characteristics can increase or decrease the phonetic prominence of a sign in a signed language, there is not yet an easily obtainable, objective measure that can be used to help quantify signal-based aspects of sign language prominence. This paper introduces a novel measure, visible amplitude, which provides a way to quantify the amount of movement contained on a frame-by-frame basis in a video, and as such, can be used as one measure of prominence. After a review of the literature that demonstrates how certain sub-lexical characteristics of signs (location, movement, and the number of hands employed) make signs 'stand out' phonetically, phonologically, and prosodically, the ability of visible amplitude to capture the effects of these characteristics is examined. It is shown that within a particular database of American Sign Language (ASL-Lex: Caselli et al., 2017), the number of hands involved in a sign's production along with movement—either transitional movement due to differences in major location, or major movement due to phonologically contrastive differences in the sign's identity—each contribute significantly to the overall visible amplitude in the sign. We review some long-standing claims about the lexical distribution of signs in light of this new measure, as well as propose possible future applications.